Natural variability and persistence in oceanic variables - Moschos, EVangelos (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Πολιτικών Μηχανικών. Τομέας Υδατικών Πόρων και Περιβάλλοντος, 2018)
Long records and reconstructions of oceanic variables as the Sea Level (SL) and the Sea Surface Temperature (SST) portray the intrinsic variability they inhibit through multiple time scales. In this study we examine the Long Term Persistence (or Long Range Dependence) that these variables exhibit by using observed and reconstructed proxies on time scales spanning from 1 month to 10 million years. We also associate their variability with periodic or oscillation processes such as the Milankovitch cycles for the SL variable and the ENSO phenomenon for the SST variable. Simple and parsimonious tools derived from Stochastic Methods, such as the climacogram and the Hurst exponent, which can be easily reproduced with basic elements of probabilities and statistics, are utilized for the purposes of this study.